C-Reactive Protein and Cognition Are Unrelated to Leukoaraiosis - Liara Rizzi; Fabricio Correia Marques; Idiane Rosset; Emilio Hideyuki Moriguchi; Paulo Dornelles Picon; Marcia Lorena Fagundes Chaves; Matheus Roriz-Cruz (The Scientific World Journal)
Elevated serum levels of C-reactive protein (CRP) have been associated with leukoaraiosis in elderly brain. However, several studies indicate that leukoaraiosis is associated with an increased risk of cognitive impairment. It is unknown how the effect of CRP on cognition is mediated by leukoaraiosis. The purpose of this study is to assess the relationship between serum levels of CRP, the presence of leukoaraiosis, and cognitive impairment in a population of coronary patients over 50 years old. CRP levels explained 7.18% (P: 0.002) of the variance of the MMSE. The adjustment for the presence of leukoaraiosis little changed this variance (5.98%, P: 0.005), indicating that only a small portion of the CRP influence on cognition was mediated via leukoaraiosis. Patients with CRP levels ≥5.0 had 2.9 (95% CI: 1.26–6.44) times more chance to present cognitive impairment (P: 0.012). We found that elevated serum levels of CRP were associated with increased risk of cognitive impairment in elderly and it was not mediated by presence of leukoaraiosis.